Design, Synthesis, and Cholinesterase Inhibitory Evaluation of Novel 5-(Benzylthio)-1,3,4-thiadiazole Derivatives - Mahmut Gozelle; Burcu Kılıç (Journal of Gazi University Health Sciences Institute, 2026)
Alzheimer's disease remains one of the leading causes of dementia, and the development of novel cholinesterase inhibitors continues to attract considerable interest for symptomatic treatment. In this study, a series of five novel 5-(benzylthio)-1,3,4-thiadiazole derivatives bearing different nitrogen-containing substituents was designed, synthesized, and evaluated for their cholinesterase inhibitory activities. The target compounds were prepared through a straightforward synthetic route involving S-benzylation of 2-amino-5-mercapto-1,3,4-thiadiazole, followed by acylation and nucleophilic substitution using various amine derivatives. All compounds were obtained in moderate to good yields and fully characterized by LC-MS, 1H NMR, and 13C NMR spectroscopy. Their inhibitory activities against acetylcholinesterase and butyrylcholinesterase were determined using a modified Ellman's assay. The synthesized derivatives generally exhibited negligible AChE inhibitory activity. In contrast, differences in the terminal amine moiety influenced BChE inhibition, with the tetrahydroisoquinoline-containing derivative, compound 4, displaying the highest activity within the series. Compound 4 showed concentration-dependent BChE inhibition, reaching 83% inhibition at 50 µM and exhibiting an IC50 value of 10.63 µM. The remaining derivatives showed little or no significant inhibition toward either enzyme under the tested conditions. These findings suggest that the tetrahydroisoquinoline scaffold may represent a promising structural motif for further optimization toward selective BChE inhibitor. Overall, this study provides a convenient synthetic platform for the development of new 5-(benzylthio)-1,3,4-thiadiazole derivatives and identifies compound 4 as a suitable lead for future structure optimization and detailed biological investigation.